Improving microstructural and mechanical characteristics of cold-sprayed Inconel 718 deposits via local induction heat treatment - Sun, Wen (2020)
In order to improve the quality of cold sprayed Inconel 718 coatings, post heat treatment is an essential procedure. However, traditional furnace heat treatment methods present some disadvantages such as low efficiency and oxidation issues. This study presented a novel strategy for post heat treatment of cold sprayed Inconel 718 coatings by using eddy current to generate heat as well as electron migration. The as-sprayed and heat-treated Inconel 718 coatings were analyzed by using optical microscopy, scanning electron microscopy (SEM), X-ray diffraction (XRD) and transmission electron microscopy (TEM). The mechanical properties of the coatings were characterized by three-point bending tests. The TEM analyses indicated that the as-sprayed Inconel 718 coating possessed a high density of dislocations and {111} <11-2> twin bands due to a high degree of plastic strain. The results also showed that the eddy current field during the heat treatment could promote atomic motions and assist recovery of the severely deformed splats, thus resulting in a significant reduction in dislocation density within the cold sprayed IN718 coatings. Besides, the induction heat treatment increased the flexural strength and ductility of the cold sprayed IN718 coatings due to that the eddy current promoted mass transport between the splats. Therefore, the induction heat treatment is a promising method for locally heat treating cold spray repaired areas.